2002
DOI: 10.1109/7.993237
|View full text |Cite
|
Sign up to set email alerts
|

Three-phase rectifiers that apply optimal current injection

Abstract: A class of current injection based three-phase high power factor rectifiers is proposed. Low distortion of the input currents and high power factor are obtained applying near optimal current injection. The optimal current injection is discussed, and requirements it imposes to the current injection network are derived. A class of simple current injection networks that provide near optimal current injection, consisting of a transformer, two capacitors, and a number of resistors or resistance emulators is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…References [35] and [36] discuss switching power converters utilized as resistance emulators. In references [25] and [28] complete power is processed by the switching converters.…”
Section: Scope Of the Bookmentioning
confidence: 99%
See 1 more Smart Citation
“…References [35] and [36] discuss switching power converters utilized as resistance emulators. In references [25] and [28] complete power is processed by the switching converters.…”
Section: Scope Of the Bookmentioning
confidence: 99%
“…Basic principles of the optimal current injection are presented in Chapter 7. The author of this book has published some ideas about the optimal current injection in [25], [26], [28], [29], and [35], while the waveforms of the diode bridge load currents that provide purely sinusoidal input currents can also be found in [22], [45], [47], and [48]. Current injection networks that provide the optimal current injection are presented in Chapter 8, which also provides systematized and expanded results of [26] and [35].…”
Section: Overview Of the Bookmentioning
confidence: 99%
“…9. A carefully designed RLC network can achieve the optimum condition too (22) . The expanded currentinjection rectifiers with the passive injection-current-source have been included in the THC-Inj (in the box "B" in Fig.…”
Section: Expanded Topologies ("B" and "A/b" Inmentioning
confidence: 99%
“…1) As mentioned, the THC-Inj has been proposed first by Bird using a sinusoidal injection current waveform (15) . Afterward, it has been found that the input line-current waveform (with THD of 5%) in the early THC-Inj rectifiers can be improved (even to a purely sinusoidal one for a particular case) by means of a quasi-triangular injection current (22) (29)- (31) . However, the optimum waveform of the injection current to achieve purely sinusoidal line-currents has been explored in the single 3-phase bridge THC-Inj rectifiers with active current-injection-source (i.e., a PWM dc-dc converter; discussed later in Section 2.3) first (29)- (31) and afterwards in the single 3-phase bridge THC-Inj rectifiers with passive currentcurrent-source (i.e., a RLC network) (22) .…”
Section: Expanded Topologies ("B" and "A/b" Inmentioning
confidence: 99%
“…The modulation and injection circuits can be either passive or active. The use of a passive modulation circuit yields generally an acceptable power factor at the expense of a non-regulated DC load voltage [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In addition, the absence of hardcommutated power switches such the ones used in active modulation circuits makes the passive circuit more reliable and more suitable to high VA rating applications.…”
Section: Introductionmentioning
confidence: 99%